2019
DOI: 10.1097/bpo.0000000000000948
|View full text |Cite
|
Sign up to set email alerts
|

Toddler’s Fractures: Time to Weight-bear With Regard to Immobilization Type and Radiographic Monitoring

Abstract: Level III-this is a retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 19 publications
2
69
0
Order By: Relevance
“…Bauer et al analyzed the different immobilization types in regard to full weight-bearing in the context of toddler's fractures and found no differences between the immobilization strategies such as long leg cast, short leg cast, boot or long leg splint. After 4 weeks in 98% of patients weight-bearing was reported (20), which is confirmed by our results (Figure 5F). Further age dependency of full weight-bearing can only by observed between the group of 5-10 to 11-17 years old.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Bauer et al analyzed the different immobilization types in regard to full weight-bearing in the context of toddler's fractures and found no differences between the immobilization strategies such as long leg cast, short leg cast, boot or long leg splint. After 4 weeks in 98% of patients weight-bearing was reported (20), which is confirmed by our results (Figure 5F). Further age dependency of full weight-bearing can only by observed between the group of 5-10 to 11-17 years old.…”
Section: Discussionsupporting
confidence: 91%
“…Toddler's fracture, as defined in 1964, is a non-displaced, isolated, distal-third diaphyseal spiral tibial fracture in children between 9 months and 3 years of age (18) and therefore constitutes the main part of the age group from 0 to 4 years, as presented in Figures 2A,B, followed by the oblique fracture of the tibia (42t-D/5.1 and 42t-D/5.2). Although the correction potential in this age group is up to 10 degrees valgus and 5 degree varus (19)(20)(21), toddler's fracture does not show any significant dislocation and conservative therapy is always indicated.…”
Section: Discussionmentioning
confidence: 91%
“…Follow-up imaging may indeed be unnecessary as we and others have questioned. 6,7 No study to date (ours included), however, has studied this directly. We therefore advocate for orthopaedic referral and evaluation of all patients with toddler's fractures, especially considering the erroneously expanded definition in the medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, recent studies support management of these stable fractures in a CAM boot (Figure 6). 32,33 Bauer et al 33 showed excellent outcomes with CAM boot immobilization compared with short leg casting and support the management of toddler’s fractures by PCPs using a CAM boot. Return to activity is typically 6 weeks and can be determined by the patient’s symptoms.…”
Section: Toddler’s Fracturesmentioning
confidence: 92%
“…The patient will usually return to full weight bearing on their own by 4 weeks. 33 Follow-up can be arranged according to parent preference if needed. 33…”
Section: Toddler’s Fracturesmentioning
confidence: 99%